Survey of glycine-rich proteins (GRPs) in the Eucalyptus expressed sequence tag database - Bocca, Sílvia Nora (2005)
The occurrence of quasi-repetitive glycine-rich peptides has been reported in different organisms. Glycine-rich regions are proposed to be involved in protein-protein interactions in some mammalian protein families. In plants, a set of glycine-rich proteins (GRPs) was characterized several years ago, and since then a wealth of new GRPs have been identified. GRPs may have very diverse sub-cellular localization and functions. The only common feature among all different GRPs is the presence of glycine-rich repeat domains. The expression of genes encoding GRPs is developmentally regulated, and also induced, in several plant genera, by physical, chemical and biological factors. In addition to the highly modulated expression, several GRPs also show tissue-specific localization. GRPs specifically expressed in xylem, phloem, epidermis, anther tapetum and roots have been described. In this paper, the structural and functional features of these proteins in Eucalyptus are summarized. Since this is the first description of GRPs in this species, particular emphasis has been given to the expression pattern of these genes by analyzing their abundance and prevalence in the different cDNA-libraries of the Eucalyptus Genome Sequencing Project Consortium (ForEST). The comparison of GRPs from Eucalyptus and other species is also discussed.